Peningkatan Kinerja Operations Pada Perusahaan E-Commerce Enabler Indonesia PT XYZ - Akbar, Henu; R, Safitri Heny; Syamil, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to explain the increase in operating performance at the E-Commerce Enabler PT. XYZ. The current condition of PT. XYZ into several parts such as operationally. The business process carried out by PT XYZ is still manual, one of which is using google docs. The biggest problem with this company is the high number of canceled orders, this is because many processes are not going well. The consultation project aims to provide recommendations for business process improvement strategies from the operational management side of PT XYZ in order to increase client satisfaction. The analysis of this research is divided into two parts, the first theory analysis and validation analysis which includes data and interviews. The results showed 1) The main mistakes that occurred in the company PT. XYZ is the delivery of Service Level Agreement (SLA) that is not as expected. 2) Not achieving the Service Level Agreement (SLA) causes the canceled order value to increase. 3) To find out the root cause of the non-conformity of the Service Level Agreement (SLA) is to use the theory of Business Process Management (BPM).